Evaluación del efecto de índices de poscosecha con tres temperaturas y dos atmósferas modificadas en el cultivo de cebolla blanca (Allium fistulosum l.) en la provincia de Cotopaxi 2015 - Caiza Caiza, Irma del Carmen (2016)
Branch onion (Allium fistulosum L.) is considered the vegetable in Ecuador and the world as the most important for their utility in the traditional kitchen in order to prepare a variety of dishes and their nutritional value in demonstrating growth years and more than 50% performance being the main producing cities Pichincha and Tungurahua. As production and performance nutritional value is lost at the time of the distribution chain from the producer to the final consumer for which this project aims to study conservation and optimum temperature to ensure longer prevalence of white onion which a laboratory study with 3 temperature types of 4 ° C, 8 ° C and room temperature with 1 and 2 diameters and roll pack packaging and wax implant obtaining 12 possible treatments taking periodic samples to measure pH,....